Notes on the suboptimality result of J. D. Geanakoplos and H. M. Polemarchakis (1986) - Jimenez Martínez, Antonio (Estudios Económicos de El Colegio de México, 2007)
J.D. Geanakoplos and H.M. Polemarchakis (1986) prove the generic constrained suboptimality of equilibrium allocations in two period economies with incomplete markets. They perturb asset prices at equilibrium when the degree of market incompleteness equals one. Since prices do not parameterize the economy, a generic result cannot be obtained in such way. These notes provide a detailed version of their proof in which utilities and endowments are perturbed.